Utilization of postnatal care services and its associated factors among women in a tertiary health care center in central India: a cross sectional study - I., Akash Gopi U.; Thakre, Sushama S.; Narlawar, Uday W.; Thakre, Subhash B.; P., Ajaya Krishnan; R., Shilpa S.; Sanjeev, Bembade S.; Barela, Shamvel A. (International Journal Of Community Medicine And Public Health, 2025)
Background: The postnatal period, lasting six weeks after childbirth, is a crucial time for mothers and newborns, requiring proper care for recovery and well-being. The World Health Organization (WHO) recommends postnatal care within 24 hours of delivery, with three follow-up visits, but uptake remains low in South East Asia, especially India. India accounts for 20% of global maternal deaths, with many preventable through better healthcare access. This study aims to assess postnatal care utilization and related factors in a tertiary healthcare center in central India. Methods: A cross-sectional study was conducted from January 1st to February 28th, 2025, among 260 postnatal women. Data was collected through face-to-face interviews using a semi-structured questionnaire. Univariate and bivariate analysis method was adopted in this study. A p value of less than 0.05 was considered statistically significant. Results: The study included 260 postnatal women, with the majority (41.16%) aged 26-30 years. Adequate postnatal care (PNC) was received by 28.4%, including breastfeeding counselling (74.23%) and newborn care advice (65.76%). Bi-variate analysis revealed significant associations between PNC utilization and some of the factors like, residence, socioeconomic status, parity, place and mode of delivery, obstetric history, and complications. Conclusions: The study found that only 28.4% of women received adequate postnatal care, with notable gaps in maternal recovery support, postnatal exercises, and family planning counselling. Enhancing awareness, increasing accessibility, and implementing focused public health interventions are crucial to improve postnatal care coverage and outcomes for mothers and newborns.